A theoretical classification of helping behavior and helping motives. Issue 5 (1st August 2016) - Chou, Shih Yung; Stauffer, Joseph M.
Abstract : Purpose: – The purpose of this paper is to develop a new classification of helping behavior using the recipient's solicitation and the helper's proactiveness. Additionally, the authors explore helping motives for each of the forms of helping behavior that the authors identify. Design/methodology/approach: – The authors examined relevant research and performed a theoretical analysis. Findings: – The authors classified helping behavior into three distinct forms, including unsolicited proactive helping behavior, unsolicited reactive helping behavior, and solicited reactive helping behavior. Additionally, the authors claimed that unsolicited proactive helping behavior is an outcome of personality and dispositions, that unsolicited reactive helping behavior is a process of social and instrumental exchange, and that solicited reactive helping behavior is a product of functional motives. Practical implications: – First, from the perspective of organizational justice, the authors recommend managers to take the form of helping behavior exhibited into consideration when evaluating employees' helping behavior because certain forms of helping behavior require greater degrees of cooperation and sacrifices from the helper than other forms. Second, because employees who engage in high levels of unsolicited proactive helping behavior are likely to experience interrole conflict, the authors suggest that managers provide counseling and managerial support that help cope with emotional and psychological strain created by excessive role demands. Finally, findings of this study imply that managers need to create a workplace culture where employees can feel comfortable to solicit help when necessary. Originality/value: – This is the first study that classifies helping behavior and helping motives using both of the helper's and recipient's perspectives.